Reconstruction of ancestral plant genomes for inter-crop translational research - Cléa Siguret; Margaux Olivier; Cécile Huneau; Mamadou Dia Sow; Pierre-Louis Stenger; Christophe Klopp; Marie-Laure Martin; Jean-Philippe Tamby; Serguei Gorbounov; Raphael Flores; Fabrice Legeai; Matéo Boudet; et al. (Molecular Plant, 2026)

Marine plastic debris as a reservoir and vector of antibiotic-resistant pathogens: evidence of transmission to sea turtles in the Southwest Indian Ocean - Philippe Jourand; Alice Philippe; Loris Carret; Shiva Moutoucomarapoule; Celia Crespel; Leila Leon; Loik Sababadichetty; Margot Thibault; Clarisse Majorel; François Guilhaumon; Véronique Lenoble; Claire Jean; et al. (Marine Environmental Research, 2026)

Resource partitioning among small pelagic fish remains stable regardless of food availability in a seasonally pulsed upwelling system - Fany Sardenne; Carl D. van der Lingen; Marie Vagner; Yonela Geja; Eleonora Puccinelli; Margaux Mathieu-Resuge; Fabienne Le Grand; Jean-Marie Munaron; Manon Buscaglia; Sandrine Serre; Philippe Soudant; Laure Pecquerie (Progress in Oceanography, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Integration of the exposome concept into health risk assessments: a challenge for health safety agencies - Amélie Crépet; Philippe Quénel; Jeanne Garric; Alain Kaufmann; Jean-Marc Bonmatin; Pascale Duché; Aurélie Mathieu; Madeline Carsique; Julien Jean; Pascal Sanders; Jean-Pierre Cravedi; Matthieu Schuler; et al. (Environmental Research, 2025)

Effects of dietary camelina oil intake on skeletal muscle metabolism and sarcopenia in older mice - Jean-Paul Rigaudière; Christophe Montaurier; Philippe Denis; Olivier Le Bacquer; Mathieu Rambeau; Chrystèle Jouve; Julia Soullier; Justine Bertrand-Michel; David M. Mutch; Frederic Capel (Journal of Physiology and Biochemistry, 2025)

Geochemical investigations of metal bioaccumulation in oysters along the land-sea continuum: Sources, fluxes and reactivity in the Seudre Estuary (France) - Jean Rillard; Julien Mathieu; Loïc Lalague; Anne Marie Desaulty; Jean Philippe David (Science of The Total Environment, 2025)

Expanding Monitoring Capacity for Potential Invasive Species in Arctic Canada With Environmental DNA Metabarcoding - Elizabeth Boyse; Melody S. Clark; Ian M. Carr; Alison J. Cook; Philippe Archambault; Jean E. Holloway; Zhewen Luo; Michael Milton; Mathieu Roy; Jackie Dawson; Victoria L. Peck (Global Change Biology, 2025)
To date, environmental conditions have been enough to act as an effective barrier to prevent non‐indigenous species from arriving and establishing in Arctic Canada. However, rapidly changing climatic conditions are creating more suitable habitats for non‐indigenous species to potentially establish and become invasive. Concurrently, shipping traffic in parts of Arctic Canada has increased by over 250% since 1990, providing an effective vector for transporting non‐indigenous species to the region. Arctic Canada has been historically undersampled, so Arctic biota inventories are incomplete, hampering efforts to establish if a species is new to the region (and potentially invasive) or newly discovered. In this study, we utilize environmental DNA (eDNA) metabarcoding and ships of opportunity to assess eukaryotic community composition and potential invasives along one of the busiest shipping routes, the Northwest Passage. One liter seawater samples were collected in triplicate at 27 locations, targeting touristic hotspots frequently visited by passenger vessels. Eukaryotic DNA was amplified from the 18S rRNA V9 and COI regions, resulting in 126 unique Amplicon Sequence Variants (ASVs) detected with COI and 391 ASVs with 18S, providing an important snapshot of current community composition. Copepods, dinoflagellates, and diatoms were the most abundant taxonomic groups, correlating well with previous net sampler surveys, validating the efficacy of eDNA for biodiversity surveillance. We also report the first detections of a prolific invasive species, the bay barnacle ( Amphibalanus improvisus ), in Arctic Canada. Further work is currently in progress to establish whether these detections represent transient barnacle larvae or sessile adults capable of recruiting and reproducing. Our study demonstrates the utility of eDNA for the detection of non‐indigenous species in a data‐poor area, which, if combined with citizen science initiatives and local communities, could provide a vital monitoring tool for the detection of new invasives in this rapidly changing area.

From planning to implementation: a multi-stakeholder partnership for managing plant invasions in tropical island ecosystems - Mathieu Rouget; Pauline Fenouillas; Emilie Cazal; Margot Caubit; Cédric Ajaguin Soleyen; Eve Balard; Antoine Becker-Scarpitta; Laurent Calichiama; Gael Karczewski; Christophe Lavergne; Benoît Lequette; Roxane L’Horset; et al. (Biological Invasions, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Tectono-sedimentary evolution of the Suriname margin in the cretaceous: A sequence-stratigraphic framework - V. Delhaye-Prat; Julien Bourget; Gwladys Gaillot; Jérémie Gaillot; François Sapin; Charlotte Fillon; Jing Ye; Tim Wright; Anne-Claire Chaboureau; Nicoletta Buratti; Benoit Magnier; Andrei Belopolsky; et al. (Earth-Science Reviews, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Deep behavioral impairment in the pearl oyster Pinctada radiata exposed to anthropogenic noise and light stress - Mohcine Charifi; Razan Khalifa; Bruno W. Giraldes; Mohamedou Sow; Zainab Hizam; Mathieu Carrara; Eric Maneux; Shafeeq Hamza; Anne Bassères; Philippe Blanc; Alexandra Leitão; Jean-Charles Massabuau (Frontiers in Marine Science, 2023)
The pearl oyster Pinctada radiata is an iconic species in the Arabian Gulf, which is one of the ecosystems most at risk in the world because of the multiple sources of pollution it faces. Alongside chemical pollution, the Gulf is ranked first with regard to noise and light pollution, and pearl oyster populations are at risk. The impact of these latter types of pollution on marine invertebrates is still poorly known. We used the difference in noise and brightness that can exist between a very quiet room without artificial lighting and a standard laboratory room equipped with a standard aquarium as a testbed to explore the possible impact of noise and light pollution on the behavioral and biological traits of Pinctada radiata without added chemical exposure. During an experiment that lasted 2.5 months, we analyzed their grouping behavior, valve activity, biological rhythm, growth rate and spawning activity. In the standard aquarium kept in the laboratory room, the oysters dispersed instead of regrouping as in their natural environment, regrouping which was observed in the quiet room. They stayed closed longer, the opening amplitude of their valves was systematically lower, and in the closed position, they squeezed their valves more tightly when subjected to noise and light pollution. Their daily opening rhythm was strongly structured by switching the electric light on and off, and females showed significantly less egg-laying behavior. In conclusion, seemingly innocuous human activities can lead to very significant alterations in pearl oyster behavior. We propose that it could have significant effects on populations and ecosystems.

Distribution of [11C]-JNJ-42491293 in the marmoset brain: a positron emission tomography study - Min Su Kang; Adjia Hamadjida; Dominique Bédard; Stephen G. Nuara; Jim C. Gourdon; Stephen Frey; Arturo Aliaga; Karen Ross; Robert Hopewell; Hussein Bdair; Axel Mathieu; Christine Lucas Tardif; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Olive mill solid waste gasification in a pilot-scale downdraft gasifier with three-stage air supply: performance, mass-energy balance and fate of inorganic elements - Gaëlle Ducom; Jean-Philippe Tagutchou; Mathieu Gautier; Carole Gaignaire; Jacques Méhu; Rémy Gourdon (Fuel, 2023)

Hydrogeochemical processes of critical zone developed in Tégulines Clay, Paris Basin: Hydrogeochemical and multi-isotopic approach (δ13C, δD, δ18O, 87Sr/86Sr and 14C) - Catherine Lerouge; Mathieu Debure; Ana-Maria Fernández; Philippe Négrel; Benoit Madé; Nicolas Maubec; Christine Fléhoc; Catherine Guerrot; Michaela Blessing; Benoit Henry; Jean-Charles Robinet (Journal of Hydrology, 2023)

Persistent organochlorine pesticides in periprostatic adipose tissue from men with prostate cancer: Ethno-geographic variations, association with disease aggressiveness - Jean-Philippe Antignac; Sandy Figiel; Michèle Pinault; Pascal Blanchet; Franck Bruyère; Romain Mathieu; Souhil Lebdai; Georges Fournier; Jerome Rigaud; Karine Mahéo; Philippe Marchand; Ingrid Guiffard; et al. (Environmental Research, 2023)

The Geotouristic Project “the Geological Adventure” to the Rescue of an Iconic World Heritage Geosite, the Ammonites Slab of Digne-les-Bains (National Geological Nature Reserve of Haute-Provence and Unesco Global Geopark, France) - Didier Bert; Violaine Bousquet; Myette Guiomar; Francesco Bariani; Jean-Claude Hippolyte; Philippe Bromblet; Jean-Luc Garciaz; Jules Fleury; Patrick Mathieu; Jean-Simon Pagès; Pierre Tardieu; Maud Dupuis-Caillot; et al. (Geoheritage, 2022)

Mapping Vernal Pools Using LiDAR Data and Multitemporal Satellite Imagery - Mathieu Varin; Philippe Bournival; Jean Fink; Bilel Chalghaf (Wetlands, 2021)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Correction to: Using Causal Inference in Field Development Optimization: Application to Unconventional Plays - Antoine Bertoncello; Georges Oppenheim; Philippe Cordier; Sébastien Gourvénec; Jean-Philippe Mathieu; Eric Chaput; Tobias Kurth (Mathematical Geosciences, 2020)

Using Causal Inference in Field Development Optimization: Application to Unconventional Plays - Antoine Bertoncello; Georges Oppenheim; Philippe Cordier; Sébastien Gourvénec; Jean-Philippe Mathieu; Eric Chaput; Tobias Kurth (Mathematical Geosciences, 2020)
In the current era of big data and machine learning, a strong focus exists on prediction and classification. In industrial applications, however, many important questions are not about prediction or classification; rather, they are causal: if I change A, what will happen to B? Traditional regression techniques such as machine learning optimize predictions based on correlations seen in the data and are not robust tools for epidemiologists and biostatisticians when evaluating the efficacy of new treatments or medications using observational data. Therefore, a set of statistical tools have been developed to go beyond correlations and aim to make inferences about causal relationships between variables. The goal of the present work is to apply one of these statistical tools, propensity score matching, in the oil and gas context, which is a novel application of the method. Two case studies are presented, one on proppant type and the other on lateral length, to determine their respective impacts on productivity.

Impact of reanalysis boundary conditions on downscaled Atlantic hurricane activity - Jean-Philippe Baudouin; Louis-Philippe Caron; Mathieu Boudreault (Climate Dynamics, 2019)

Can one detect atrial fibrillation using a wrist-type photoplethysmographic device? - Sibylle Fallet; Mathieu Lemay; Philippe Renevey; Célestin Leupi; Etienne Pruvot; Jean-Marc Vesin (Medical & Biological Engineering & Computing, 2019)

Noninvasive pulmonary artery pressure monitoring by EIT: a model-based feasibility study - Martin Proença; Fabian Braun; Josep Solà; Jean-Philippe Thiran; Mathieu Lemay (Medical & Biological Engineering & Computing, 2017)

Tropical Shearwater population stability at Reunion Island, despite light pollution - Benoit Gineste; Mathieu Souquet; François-Xavier Couzi; Yannick Giloux; Jean-Sébastien Philippe; Cedric Hoarau; Julie Tourmetz; Gaël Potin; Matthieu Le Corre (Journal of Ornithology, 2017)

Genetic and platelet function testing of antiplatelet therapy for percutaneous coronary intervention: the ARCTIC-GENE study - Jean-Philippe Collet; Jean-Sébastien Hulot; Thomas Cuisset; Grégoire Rangé; Guillaume Cayla; Eric Van Belle; Simon Elhadad; Hélène Rousseau; Pierre Sabouret; Stephen A. O’Connor; Jérémie Abtan; Mathieu Kerneis; et al. (European Journal of Clinical Pharmacology, 2015)

Meta-analysis for the transfer of economic benefits of ecosystem services provided by wetlands within two watersheds in Quebec, Canada - Jie He; Fanny Moffette; Richard Fournier; Jean-Pierre Revéret; Jérôme Théau; Jérôme Dupras; Jean-Philippe Boyer; Mathieu Varin (Wetlands Ecology and Management, 2015)

Prasugrel but not high dose clopidogrel overcomes the lansoprazole neutralizing effect of P2Y12 inhibition: Results of the randomized DOSAPI study - Jean-Philippe Collet; Jean-Sébastien Hulot; Jérémie Abtan; Ghalia Anzaha; Mathieu Kerneis; Johanne Silvain; Guillaume Cayla; Stephen A. O’Connor; Olivier Barthélémy; Farzin Beygui; Sophie Galier; Delphine Brugier; et al. (European Journal of Clinical Pharmacology, 2014)

Stimulation of Different Functional Groups of Bacteria by Various Plant Residues as a Driver of Soil Priming Effect - Noémie Pascault; Lionel Ranjard; Aurore Kaisermann; Dipankar Bachar; Richard Christen; Sébastien Terrat; Olivier Mathieu; Jean Lévêque; Christophe Mougel; Catherine Henault; Philippe Lemanceau; Michel Péan; et al. (Ecosystems, 2013)

Precipitation and temperature space–time variability and extremes in the Mediterranean region: evaluation of dynamical and statistical downscaling methods - Emmanouil Flaounas; Philippe Drobinski; Mathieu Vrac; Sophie Bastin; Cindy Lebeaupin-Brossier; Marc Stéfanon; Marco Borga; Jean-Christophe Calvet (Climate Dynamics, 2013)

Alpha7-nicotinic receptors modulate nicotine-induced reinforcement and extracellular dopamine outflow in the mesolimbic system in mice - Morgane Besson; Vincent David; Mathieu Baudonnat; Pierre Cazala; Jean-Philippe Guilloux; Christelle Reperant; Isabelle Cloez-Tayarani; Jean-Pierre Changeux; Alain M. Gardier; Sylvie Granon (Psychopharmacology, 2012)

Sensitivity to domain size of mid-latitude summer simulations with a regional climate model - Martin Leduc; René Laprise; Mathieu Moretti-Poisson; Jean-Philippe Morin (Climate Dynamics, 2011)

The Planeterrella, a pedagogic experiment in planetology and plasma physics - Jean Lilensten; Mathieu Barthélemy; Cyril Simon; Philippe Jeanjacquot; Guillaume Gronoff (Acta Geophysica, 2009)

Fluorescence Study of Lipid-based DNA Carriers Properties: Influence of Cationic Lipid Chemical Structure - Laure Burel-Deschamps; Mathieu Mével; Damien Loizeau; Farouk Ayadi; Jean-Jacques Yaouanc; Jean-Claude Clément; Paul-Alain Jaffrès; Philippe Giamarchi (Journal of Fluorescence, 2008)

Topology-based abstraction of complex biological systems: application to the Golgi apparatus - Mathieu Poudret; Agnès Arnould; Jean-Paul Comet; Pascale Le Gall; Philippe Meseure; François Képès (Theory in Biosciences, 2008)

A multi-scale study of soil macrofauna biodiversity in Amazonian pastures - Jrme Mathieu; Jean-Pierre Rossi; Michel Grimaldi; Philippe Mora; Patrick Lavelle; Corinne Rouland (Biology and Fertility of Soils, 2004)

Number and size of nevi are influenced by different sun exposure components: implications for the etiology of cutaneous melanoma (Belgium, Germany, France, Italy) - Philippe Autier; Gianluca Severi; Remy Pedeux; Maria-Sofia Cattaruzza; Mathieu Boniol; André Grivegnée; Jean-François Doré (Cancer Causes & Control, 2003)